Adapting the low carbon cities framework for Saudi Arabia: a comparative assessment of Riyadh and Jeddah under Vision 2030 and implications for sustainable social housing - Hegazy, Ibrahim; Imam, Ayman (Frontiers in Built Environment, 2026)
IntroductionRapid urbanization and extreme aridity in Gulf cities pose unique decarbonization challenges that generic global sustainability frameworks fail to address, particularly in guiding the development of sustainable, resilient social housing in Saudi Arabia’s major metropolitan regions. This study addresses the need for a context-sensitive performance metric that links city-scale infrastructure to the affordability and resilience of housing communities.MethodsWe developed and applied the Low Carbon Cities Framework for Saudi Arabia (LCCF-SA)—a localized adaptation of Malaysia’s Low Carbon Cities Framework tailored to the Kingdom’s reliance on energy-intensive desalination and extreme cooling demand. The framework was calibrated through a two-round Delphi process involving 15 experts to align indicator weights with Vision 2030 priorities. It was compared between Riyadh and Jeddah across 16 indicators in four domains (Urban Environment, Transportation, Infrastructure, Buildings), operationalized using 2018–2024 municipal, utility, and national datasets, along with GIS-based spatial analysis. Indicator values were transformed to a 0–100 scale using min–max normalization, aggregated into domain and composite city scores with Delphi-derived weights, and tested through alternative weighting scenarios to assess the robustness of the Riyadh–Jeddah comparison.ResultsFindings reveal a distinct performance divergence: Riyadh consistently attains higher domain and overall LCCF-SA scores than Jeddah, outperforming it in all 16 LCCF-SA indicators, driven by centralized governance and large-scale investments in metro transit, green infrastructure, and utility upgrades. Jeddah, by contrast, is constrained by coastal flood vulnerabilities, higher non-revenue water, and more fragmented planning. However, both cities exhibit systemic underperformance in residential retrofitting (<5%) and in active mobility, creating an “affordability trap” in which car dependency, inefficient building envelopes, and desalination-intensive water supply significantly inflate long-term housing operating costs for low-income residents.DiscussionThe analysis demonstrates that city-scale infrastructure performance is a non-negotiable prerequisite for housing resilience and long-term affordability. The study makes three key contributions: (i) it provides the first systematically localized low-carbon framework for hyper-arid, desalination-dependent cities in the Gulf; (ii) it reframes low-carbon metrics as “affordability indices” that link transport, energy, and water performance directly to the economic viability of social housing; and (iii) it offers a transparent, replicable site-selection and benchmarking tool to prioritize social housing projects in resilient, transit-connected, and infrastructure-efficient urban systems.